Exploring the diversity and ecology of bacteriophages in the dairy farm environment - Cook, Ryan (2023)
Bacteriophages, viruses that obligately infect bacteria, represent the most abundant and diverse biological entities on the planet, with key and complex ecological roles in all environments where they have been studied. Agricultural wastes and manures (i.e., cattle slurry) are economically important fertilisers that are applied to land. Despite the widespread use of slurries, there is a paucity of knowledge regarding the microbial composition within them. The first part of this thesis sought to optimise viral metagenomics, for the study of viral communities in nature. As the study of uncultivated viral genomes is underpinned by known complete viral genomes, I assessed the current extent of viral sequencing to provide the most complete reference database possible in an updated and reproducible fashion. This led to the INPHARED database, now published in PHAGE and available on GitHub; a community resource that provides genomes and annotation files to aid in viral genomic and metagenomic analyses. Furthermore, I investigated biases in the current collection of phage genomes and demonstrated that clear biases towards phages of a small subset of clinically relevant bacteria. Subsequently, I sought to benchmark sequencing technologies and assembly approaches for the recovery of viral genomes from viral metagenomes. This work, in part published in Microbiome and under review in Microbial Genomics, demonstrated that choice of sequencing technology and assembly algorithm will have significant impacts on downstream analyses and estimates of viral diversity. Overall, these analyses demonstrated that a combination of long and short read sequencing approaches performed best at recovering viral genomes in a mixed community.